The system of training future teacher for the formation of pupils’ thinking - Shamurat Orazov, Ulbossyn Baimanova, Jamilya Torybayeva,; Nuridinova, Guldana; Alipbek, Ardak (Opción, 2019)
The aim of the present study was the provision and development of a theoretical basis for a system of training future teachers to form pupils’ critical thinking via comparative quantitative research methods. The questionnaire results showed a low level of students’ critical thinking formation, their responses lacked the main substantive-formal basis, the very essence of critical thinking. In conclusion, systematic representations about the continuity of stages and levels of forming students’ critical thinking and, correspondingly, the role and functions of higher education institution teachers allowed considering the systemic nature of developing future teacher’s critical thinking experience.